Trends in audiences studies published in academic communication journals from Argentina - Heram, Yamila (2025)
This article analyzes the main trends in audience research studies published in scientific journals on communication from Argentina (2016-2020). Following the meta-research tradition, we made content analysis. The corpus consists of a total of 51 articles. The main results demonstrate the prevalence of inductive and empirical studies, and a preference for studying audiences in relation to digital consumptions in young age groups. We also observed signs of fragmentation and dispersion in the methodological aspects. Most articles were written in South America by unique signatories. The main challenge has audience studies is the need to work on conceptualization, to be able to reflect from a critical and contextual perspective, to advance the study of invisible generational groups, and to re-examine the place of traditional media. It is urgent to rethink audiences in a context of strong media concentration where the power between mass media and audience is as disproportionate as it is unequal. Between inequality and power, we can find the reason for study audiences.